VALIDASI KLINIK GENERAL HEALTH QUESTIONNAIRE-12 SEBAGAI INSTRUMEN SKRINING GANGGUAN SOMATOFORM DI PUSKESMAS - , Salma; , Rahmat Hidayat, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Somatoform disorder is one of the high prevalent mental health problems and one that is common among patients of Primary Care, including Pusat Kesehatan Masyarakat (Puskesmas). However, there is no valid, reliable, sensitive, and specific screening instrument available in Primary Care to detect somatoform disorder in Indonesia. This study aimed to examine clinical validity of GHQ-12 through Structured Clinical Interview for DSM IV Disorder-Axis I (SCID-I) as a gold standard and consider GHQ-12 as screening instrument of somatoform disorder in Primary Care setting. Data of 250 patients from 11 Primary Care institutions in Sleman and Kota Yogyakarta District were collected as sample. Of the 215 complete data of patients, there were 57 (26.51%) patients diagnosed by Somatoform Disorders (SDs).The Alpha Cronbach Reliability coefficient were satisfactory according to bimodal, Likert, and c-GHQ scoring methods (0.863, 0.893, and 0.854 respectively). Principal Component Analysis (PCA) yielded two components of GHQ-12, namely âpsychological distressâ and âsocial dysfunctionâ. Receiver Operating Curve (ROC) analysis applied and revealed Area Under the Curve (AUC) between 65.1-66.6% for three different scoring method. The optimum cut-off score was >5 using Likert scoring method with a sensitivity of 73.7% and a specificity of 54.4%. LR+ and LR- were 1.62 and 0.48 respectively. The result of this study shows that GHQ-12 can be used with caution as screening instrument of SDs in Primary Care. Further implementation is discussed.